Knowledge Capturing and Codifying in Knowledge Management Using Alfresco: A Case Study of Swiss German University - Bandoso, Charles Sosang; Ipung, Heru Purnomo; Soetomo, M. A. Amin (Swiss German University, 2015)
Knowledge management has become the asset of every organization because every knowledge in each group is unique one with another. Two aspects that important in knowledge management is step to capturing theknowledge and codifying the knowledge. Capturing mean to list or create a real documentation of knowledge while codifying is to create a digital version from capturing process so it can be processed or easily manipulated. One of the most growth software to do knowledge management for codifying is alfresco that being established in 2005. Alfresco provide open source so called Alfresco Community Edition that enable developer to create rules in codifying the knowledge. The output of this process is to create functional ECM in a form of a portal where end user can use it to manage a contents or documents.